Cultural anthropology - Nanda, Serena; Warms, Richard L. (Wadsworth/Cengage Learning, 2014)
Provides fresh coverage of cultures around the world. This title is designed to increase your understanding of the human past and present, the unity and diversity that characterise the human species and how globalisation has affected the lives of people all around the world.